Attenuation measurement on cyclotene (BCB photo resin) polymer based slab waveguide - Ulaganathen, Kesavan (2005)
Photonic switch /device are widely developed due to great requirement of all optical based network. The photonic device can be further divided into active and passive devices, in which for the former one, further light controlled using electric field or temperature variation is the actual characteristic. In this project, investigation of the thermo optic properties of the existing polymer in the photonic Lab was carried out. The investigation included with the literature study on the possible ways for characterizing both properties and further an experimental set-up was included in this project. Study on the attenuation and losses of light wave when it travels through polymer slab was introduced. An experimental set-up to identity the best technique to launch the light source into the wave guide by comparing the other method been done. New improved technique of the launching the light source into the fiber slab was introduced with taking into the account of attenuation and the losses at the minimum level.